Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Dual roles of static magnetic field on enhancing sulfamethoxazole biodegradation and preventing antibiotic resistance genes transfer in halotolerant fungal-bacterial sludge treating saline aquaculture wastewater - Zhen-Ying Li; You-Wei Cui; Rui-Chun Yang; Ya-Nan Mi; Yuan Sui (Bioresource Technology, 2026)

Enhanced photothermal catalytic oxidation of cyclohexane over a S-scheme CoAl2O4/WO3-x heterojunction with LSPR effect-induced hot electrons - Kuan Wang; Kai-Xiong Dai; Yu-Rui Chao; Yue Yang; Xin-Peng Li; Zhen-Hong He; Weitao Wang; Huan Wang; Zhao-Tie Liu (Journal of Environmental Chemical Engineering, 2026)

Disintegrated halophilic aerobic granular sludge restoration using zinc oxide nanoparticles: synergistic effects of fungal toxicity inhibition and extracellular polymeric substances production - Ya-Nan Mi; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Zhen-Ying Li; Xu-Zhen Liu; Tong Ren (Bioresource Technology, 2026)

Corrigendum to “Synergistic regulation of photosynthetic efficiency at physiological and transcriptional levels in Ottelia acuminata under single and combined nitrogen and phosphorus treatments” [Biores. Technol. 446 (2026) 134212] - Xiong-Li Zhou; Ni-Fei Dai; Si-Qi Wang; Rui-Zhang; Zhen-Yu Lyu; Erik Jeppesen; Liu Yang; Shi-Kang Shen (Bioresource Technology, 2026)

Exploring the mechanism of platycodon grandiflorum saponins in treating Mycoplasma pneumoniae pneumonia based on intestinal microbiota and metabolomics - Rui Shuang Ji; Yun Fei Yang; Chan Yu Wu; Zhen Jing Yang; Jin Zhao Du; Jing Huang Fu; Lin Yao; Wei Ming Wang (Food Bioscience, 2026)

An energy-spectrum-biased auto-importance sampling method for variance reduction in Monte Carlo energy spectrum simulations - Yang Zhou; Hui Zhang; Zhen Wu; Yisheng Hao; Rui Qiu; Jiajun Wu; Jiahe Shang; Junli Li (Annals of Nuclear Energy, 2026)

CWN-Net: a precise segmentation model for composite water networks using multi-source and multi-temporal remote sensing imagery - Mingyang Li; Huimin Lei; Fulin Li; Jiwen Huang; Yuzhi Shi; Shangjie Xu; Han Wang; Sinan Wang; Rui Wang; Lili Liu; Suzhen Cheng; Lei Guo; et al. (Journal of Hydrology, 2026)

Numerical investigation on dynamic response and damage evolution of icy lunar regolith simulants - Yun-Li Li; Zhen-Rui Yang; Wen-Ping Wu (Advances in Space Research, 2026)

Corrigendum to “Preparation of multifunctional hydrogel composed of polyvinyl alcohol/ chitosan/cellulose nanofiber/anthocyanin and its application in intelligent food packaging systems” [Food Res. Int. 235 (2026) 119173] - Zhen-Zhen Lu; Jie Chen; Jing Jin; Xiao-Rui Ge; Xiao-Hui Yao; Wei-Guo Zhao; Dong-Yang Zhang (Food Research International, 2026)

Preparation of multifunctional hydrogel composed of polyvinyl alcohol/ chitosan/cellulose nanofiber/anthocyanin and its application in intelligent food packaging systems - Zhen-Zhen Lu; Jie Chen; Jing Jin; Xiao-Rui Ge; Xiao-Hui Yao; Wei-Guo Zhao; Dong-Yang Zhang (Food Research International, 2026)

Distribution profiles of 12 isoflavone monomers in Chinese soybeans from saline-alkali and ordinary soils and subsequent supercritical CO₂ extraction optimization - Zixuan Liu; Ziqian Xue; Rui Yang; Xinru Guo; Yutong Zhen; Guiqiao Liu; Chunmei Li; Bei Fan; Fengzhong Wang (Food Chemistry, 2026)

Antibacterial effect and mechanism of plasma-activated water on Salmonella Typhimurium and Listeria monocytogenes - Wenzhe Liu; Rui Gao; Luyao Zhao; Shuo Yang; Hanfeng Zhang; Zhen Jiao; Qing Chi (Food Bioscience, 2026)

Metabolic inflexibility across heart failure phenotypes: mechanisms and type-specific therapeutic implications - Li Chen; Xin-Rui Yang; Yan Jiang; Shi-Qi Cheng; Zhen-Xun Wan; Jin-Wen Wu; Ming-Tai Chen; Yuan-Yuan Li; Gang Luo; Meng-Nan Liu (Apoptosis, 2026)

Luminescence chronology of subordinate dunes on the megadunes of the Badain Jaran Desert, North China - Tianyuan Chen; Tao Lu; Siwen Liu; Rui Yang; Zhen-Ting Wang; Yixuan Wang; Qishun Fan; Zhongping Lai (Geomorphology, 2026)

Poly(terphenyl piperidinium) copolymer membranes with aryl-alkyl ether and π-conjugated butadiene segments for anion exchange membrane water electrolysis - Wenzhe Zhao; Rui Zhang; Zhen Peng; Yang Wu; Yun Zhao; Jingshuai Yang (Chemical Engineering Journal, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Data-driven assessment of nitrogen and phosphorus buffering capacity across 460 Chinese watersheds: Spatial patterns, drivers, and future projections - Yunfei Cao; He Yao; Chuang Zhang; Chaojun Gu; Lin Yang; Rui Hao; Xiao Li; Zhen Wang; Haibing Xiao; Jian Wang; Zhihua Shi (Water Research, 2026)

SB216763 enhances proliferation and sustains the undifferentiated state of porcine spermatogonial cells in prolonged In vitro culture - Benliang Zhou; Zhen Zhang; Anqin Duan; Jiaxiang Ji; Mengqi Li; Rui Chen; Xiangxing Zhu; Jianghua Shang; Xiaogan Yang; Xingwei Liang (Theriogenology, 2026)

Driving factors on bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants: Evidence from different latitudinal gradients in warm season - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Yuan Sui; Tong Ren; Xin-Yu Gu; Ming-Xin Su; Ze-You Lu (Journal of Water Process Engineering, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Synergistic regulation of photosynthetic efficiency at physiological and transcriptional levels in Ottelia acuminata under single and combined nitrogen and phosphorus treatments - Xiong-Li Zhou; Ni-Fei Dai; Si-Qi Wang; Rui-Zhang; Zhen-Yu Lyu; Erik Jeppesen; Liu Yang; Shi-Kang Shen (Bioresource Technology, 2026)

Joint Quay Crane and Automated Guided Vehicle Scheduling Optimization in Automated Container Terminals Considering Spare Battery Constraints - Zhen Yang; Rui Zhao; Yifan Shen; Xiong Zhong (Journal of Marine Science and Engineering, 2026)
With the expansion of automated container terminals (ACTs), joint scheduling among multiple types of equipment has become a critical factor affecting operational efficiency. This study investigates a joint scheduling optimization problem of quay cranes (QCs) and automated guided vehicles (AGVs) by considering AGV battery swapping strategies under spare battery constraints. With the objective of minimizing the final task completion time of AGVs, a mixed-integer programming model is formulated that simultaneously accounts for task assignment, operation sequencing, battery swapping thresholds, spare battery quantity, and mutual waiting times between AGVs and QCs. To solve this problem efficiently, a hill-climbing genetic algorithm (HC-GA) is proposed. Numerical experiments under different task scales show that HC-GA outperforms the genetic algorithm (GA), simulated annealing (SA), Q-learning, and the Q-learning-based genetic algorithm (Q-GA) in key indicators. In addition, the experimental results show that a proper configuration of AGVs can improve scheduling coordination and enhance the energy utilization efficiency of AGVs. The number of spare batteries and the threshold have significant impacts on overall system performance. When both operational efficiency and equipment utilization are considered, appropriately configuring the number of spare batteries and the threshold can effectively enhance the operational efficiency of ACTs.

Nutrient regimes shaping the diatom-dinoflagellate interdecadal succession in coastal temperate waters of China - Kan Chen; Keqiang Li; Guangshen Tan; Peiyi Gao; Guangmin Zhen; Rui Yang; Kunlong Yu; Xiansheng Zhang; Xiaoru Cui; Dongliang Lu; Shanqiao Chen; Eric P. Achterberg; et al. (Water Research, 2026)

Comprehensive evaluation on potentiality and key bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Ming-Teng Li; Yuan Sui (Process Safety and Environmental Protection, 2026)

Eucommia ulmoides leaf extract enhanced growth, supported liver and intestinal function, modulated gut microbiota composition, and increased disease resistance in juvenile largemouth bass (Micropterus salmoides) - Qiang Hao; Tsegay Teame; Rui Xia; Qianwen Ding; Yuanyuan Yao; Chao Ran; Yalin Yang; Zhen Zhang; Zhigang Zhou (Aquaculture, 2026)

Two meroterpenoids from the root bark of Eucalyptus robusta - Yi-Yang Chen; Yong-Xin Wei; Rui-Zhen Chen; Kun-Feng Zhang; Ling-Yi Kong; Ming-Hua Yang (Phytochemistry Letters, 2025)

Xylo-oligosaccharide utilization by Weissella kandleri YT103: Transcriptomic analysis and intestinal barrier protection - Xin-rui Zhang; Shuang-shuang Cui; Long-fen Yin; Gui-zhen Gong; Jian-xia Yang; Yang Chen; Yuan-ting Zhu (Food Research International, 2025)

Frititaipaines A−O, undescribed cevanine-type isosteroidal alkaloids from the bulbs of Fritillaria taipaiensis and their anti-neuroinflammatory and AChE inhibitory activities - Zai-Long Huang; En-Ke Qu; Lan-Run Yang; Rui Luo; Yan-Ni Liang; Shi-Jun Liu; Yuan-Zhen Xu; Dong-Bo Zhang (Phytochemistry, 2025)

Magnetic biochar-cored halophilic aerobic granules: Novel strategy for rapid formation and structural stability enhancement - Dong-Xu Zhou; You-Wei Cui; Ya-Nan Mi; Zhen-Ying Li; Rui-Chun Yang; Yuan Sui (Bioresource Technology, 2025)

Fatigue Behavior of Rock Salt under Primary Creep Effect at Various Temperatures with Acoustic Emission Monitoring - Hang Li; Hongling Ma; Zhiwen Hu; Zhen Zeng; Jiangyu Fang; Rui Liang; Chunhe Yang (Rock Mechanics and Rock Engineering, 2025)

Synergistic engineering of four-pointed star-like layered stacking and oxygen vacancies toward high-efficiency Bi2O2-xSe photocatalysts for the degradation of tetracycline and Congo red - Yao Yang Liu; Zhong Li; Yi Liang; Jing Hao Zhuang; Wen Ji Zhang; Tao Tang; Yin Fen Cheng; Rui Ou; Bao Yue Zhang; Jian Zhen Ou (Journal of Environmental Chemical Engineering, 2025)

Programmable protein nanofibrils for high-performance hydrovoltaic energy harvesting with electroactive bacterial cells - Rui-Jie Ma; Luyu Yang; Yang-Chun Yong; Zhen Fang (Chemical Engineering Journal, 2025)

Vapor additive strategy enabling perfect crystallization of vacuum-evaporated photovoltaic perovskites - Lei Huang; Zhang Chen; Kai-Li Wang; Zi-Hao Song; Xiao-Ying He; Zhen-Huang Su; Jing Chen; Chun-Hao Chen; Yu Xia; Yu-Tong Yang; Xin Chen; Rui-Hao Qin; et al. (Chemical Engineering Journal, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

A salt-tolerant tetracycline degrading fungal strain of Candida palmioleophila: Characterization and degradation pathway - Zhen-Ying Li; You-Wei Cui; Hui-Juan Yan; Hui-Kai Liang; Rui-Chun Yang (Journal of Hazardous Materials, 2025)

A novel forward osmosis nanocomposite membrane with g-C3N4 quantum dots fabricated on polyacrylonitrile electrospun nanofiber membrane for high-permeability and selectivity - Dibakar Pandaya; Jia-Rui Yang; Zhen-Liang Xu; Mateen Hedar; Ming-Xiao Zhang; Rui Jia; Rui Han; Muhammad Irfan; Liang Cheng; Mahesh Kumar Joshi (Chemical Engineering Journal, 2025)

“Zombie” cell drug delivery system: A novel strategy for the treatment of cancer and inflammation-related diseases - Zhouru Wang; Wenjing Yang; Danhua Liu; Peihong Lin; Rui Gao; Zhen Ma; Qiao Wang; Zhan Tang; Jie Fang; Wenying Yu (Chemical Engineering Journal, 2025)

Colletotrichum spaethianum causes leaf spot disease in Stemona japonica in the Guizhou province of China - Rui Zhang; Chengqing Yang; Dengquan Liu; Zhen Su; Zhongshun Cai; Cheng Li (Crop Protection, 2025)

Strain-specific effects of fish originated Bacillus velezensis on growth, gut health, and disease resistance of zebrafish - Yuan-Yuan Yao; Wen-Hao Zhou; Juan Hu; Ya-Lin Yang; Ming Li; Rui Xia; Chao Ran; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Molecular identification of heterotrophic nitrification and aerobic denitrification bacteria: From methods development to application demonstration - Rui-chun Yang; You-wei Cui; Zhen-ying Li; Ming-teng Li; Liu-xu Jiang; Ya-nan Mi; Yuan Sui; Hui-kai Liang (Water Research, 2025)

Tetracycline degradation by a mixed culture of halotolerant fungi-bacteria under static magnetic field: Mechanism and antibiotic resistance genes transfer - Zhen-Ying Li; You-Wei Cui; Hui-Kai Liang; Hui-Juan Yan; Rui-Chun Yang (Journal of Hazardous Materials, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Intelligently responsive PVDF MF membrane with improved antifouling and easy-cleaning performance for efficient separation of oil-water emulsion - Aida Aibulatova; Lin Yu; Zhen-Liang Xu; Jia-Rui Yang; Rui Jia; Yin-Xin Fang (Journal of Environmental Chemical Engineering, 2025)

Injectable dual-network hydrogel for phototherapy and immunomodulation in the treatment of MRSA-infected and diabetic wound - Shengfei Bao; Aodi Jiang; Li Peng; Fuying Liao; Ga Liu; Li Chen; Peng Zhou; Zhen Zhu; Rui L. Reis; Subhas C. Kundu; Lian Duan; Bo Xiao; et al. (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Omics research in atherosclerosis - Kai-Jiang Tian; Yu Yang; Guo-Shuai Chen; Nian-hua Deng; Zhen Tian; Rui Bai; Fan Zhang; Zhi-Sheng Jiang (Molecular and Cellular Biochemistry, 2025)

BarH1 regulates the expression of conserved odorant-binding protein 22 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Ao Liu; Yi Wei; Rui-Lin Zhang; Hazem Abdelnabby; Man-Qun Wang (Insect Biochemistry and Molecular Biology, 2025)

Upper Ordovician conodonts from the Taoqupo section in the southwestern margin of the North China Craton - Shi-Xiao Li; Xiu-Chun Jing; Hong-Rui Zhou; Xun-Lian Wang; Yang Shen; Qiang Fang; Zhen-Tao Wang (Palaeoworld, 2025)

TDCPP promotes apoptosis and inhibits the calcium signaling pathway in human neural stem cells - Ming-Rui Li; Guo-Rui Zhou; Zi-Ye Wang; Bo-Yang Li; Shu-Hui Men; Zhen-Guang Yan (Science of The Total Environment, 2025)

The long noncoding RNA ALEX1 confers a functional phase state of ARF3 to enhance rice resistance to bacterial pathogens - Meng-Qi Lei; Rui-Rui He; Yan-Fei Zhou; Lu Yang; Zhen-Fei Zhang; Chao Yuan; Wen-Long Zhao; Yu Cheng; Jian-Ping Lian; Yu-Chan Zhang; Wen-Tao Wang; Yang Yu; et al. (Molecular Plant, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Interfacial built-in electric field in 2D Ni(OH)2 heterojunction with the sodium organic compound for enhanced oxygen evolution catalysis - Jiao Zhou; Mingyuan Zhang; Baiyu Ren; Qian Yi; Hao Yu; Baoyue Zhang; Ang Li; Xinyi Hu; Zhong Li; Guanyu Chen; Yinfen Cheng; Rui Gao; et al. (Chemical Engineering Journal, 2025)

Construction of cellulose 3D network composite membrane supported by hydroxylated boron nitride with high surface charge density to achieve high-efficiency osmotic energy harvesting - Rongrong Zhang; Zhen Wang; Rui Zhao; Zhaoyun Lin; Chang Geun Yoo; Guihua Yang; Jiachuan Chen; Gaojin Lyu (Chemical Engineering Journal, 2024)

Assessing the role of urban green infrastructure in mitigating summertime Urban Heat Island (UHI) effect in metropolitan Shanghai, China - Hao Zhang; Meng-yuan Kang; Zhen-ru Guan; Rui Zhou; Ai-lian Zhao; Wen-jia Wu; Hao-rong Yang (Sustainable Cities and Society, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

New insights into the mechanisms and therapeutic strategies of chondrocyte autophagy in osteoarthritis - Lujia Tang; Jiatong Ding; Kangping Yang; Zhen Zong; Rui Wu; Hui Li (Journal of Molecular Medicine, 2024)

Robust control algorithm designed for robotic legs of lunar-based equipment: Modeling and experiment - Zheng-Han Chen; Zhao-Dong Xu; Rui-Heng Wang; Hong-Fang Lu; Deng-Yun Yu; Jian-Zhong Yang; Xue-Liang Zhao; Zhong-Wei Hu; Sheng-Chao Zhen (Advances in Space Research, 2024)

The Roles of Non-coding RNA Targeting Astrocytes in Cerebral Ischemia - Chun-mei Long; Zhen Li; Wang Song; Xin Zeng; Rui Yang; Li Lu (Molecular Neurobiology, 2024)

Recent progress and perspectives on coal dust sources, transport, hazards, and controls in underground mines - Yong Cao; Yang Xiao; Zhen-Ping Wang; Qing-Wei Li; Chi-Min Shu; Xing-Rui Jiang; Shi-Liang Wu (Process Safety and Environmental Protection, 2024)

Genome-wide identification of the MED25 BINDING RING-H2 PROTEIN gene family in foxtail millet (Setaria italica L.) and the role of SiMBR2 in resistance to abiotic stress in Arabidopsis - Yimin Fan; Yue Guo; Haiying Zhang; Rui Han; Pu Yang; Zhen Liang; Lizhen Zhang; Ben Zhang (Planta, 2024)

Two new sesterterpenoids from Atractylodes japonica Koidz. ex Kitam - Yuan-Yuan Zhou; Zhao Sun; Yan Liu; Zhen-Xing Fang; Hui-Rui Gao; Ning-Yu Liu; Xiao-Juan Zhang; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2024)

Effects of dietary bacterial culture of fengycin-producing Bacillus subtilis on growth performance, intestinal and hepatopancreas health, intestinal microbiota and disease resistance of common carp (Cyprinus carpio) - Rui Xia; Shenghui Li; Hongwei Yang; Yajie Zhao; Tsegay Teame; Qiang Hao; Mingxu Xie; Min Li; Qile Chen; Chunling Song; Chao Ran; Yalin Yang; et al. (Aquaculture, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Regulation of wheat growth by soil multifunctionality and metagenomic-based microbial functional profiles under mulching treatments - Yang Liu; Rui Liu; Zhen Feng; Rong Hu; Fazhu Zhao; Jun Wang (Science of The Total Environment, 2024)

Phenolic components from the fruits of Solanum xanthocarpum with anti-inflammatory activity - Yan Liu; Rui Yang; Hai-Dan Zou; Zhen-Peng Xu; Juan Pan; Jia-Tong Wu; Wei Guan; Zhi-Chao Hao; Adnan Mohammed Algradi; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2024)

Serum Uric Acid Levels and Outcome of Acute Ischemic Stroke: a Dose–Response Meta-analysis - Peng Zhang; Rui Wang; Yang Qu; Zhen-Ni Guo; Qing Zhen; Yi Yang (Molecular Neurobiology, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Improving bioelectrochemical performance by sulfur-doped titanium dioxide cooperated with Zirconium based metal–organic framework (S-TiO2@MOF-808) as cathode in microbial fuel cells - Qin Qi; Guofu Huang; Rui Li; Jiale Yu; Xiaomin Chen; Zhen Liu; Yanyan Liu; Renjun Wang; Yuewei Yang; Junfeng Chen (Bioresource Technology, 2024)

Use of a new Tibetan Plateau network for permafrost to characterize satellite-based products errors: An application to soil moisture and freeze/thaw - Jingyao Zheng; Tianjie Zhao; Haishen Lü; Defu Zou; Nemesio Rodriguez-Fernandez; Arnaud Mialon; Philippe Richaume; Jianshe Xiao; Jun Ma; Lei Fan; Peilin Song; Yonghua Zhu; et al. (Remote Sensing of Environment, 2024)

Petrogenesis and tectonic implication of the Triassic syenitic complexes in the eastern Qinling orogen, central China - Zhen-Yu Wang; Hong-Rui Fan; Hai-Dong She; Kui-Feng Yang (Journal of Asian Earth Sciences, 2024)

Three new flavones from the whole plants of Cassia auriculata Linn. and their antiviral activities - Rui-Feng Xiong; Jun-Na Zheng; Qing-Yang Wu; Ning Jiang; Yuan-Sheng He; Yong-Jun Zhang; Ben-Hui Li; Wei Li; Qiu-Fen Hu; Zhen-Yuan Xia; Yin-Ke Li (Phytochemistry Letters, 2023)

The hepatoprotective effects of plant-based foods based on the “gut–liver axis”: a prospective review - Qiongdan Hu; Wan Liao; Zhen Zhang; Sanjun Shi; Shuguang Hou; Ningping Ji; Xinjie Zhang; Qian Zhang; Yangyang Liao; Linghui Li; Zongping Zhu; Yi Chen; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Two truxinate derivatives and a phenyldilactone from the leaves of Castanopsis eyrei - Ya-feng Wang; Nao Pang; Zhen-hua Liang; Yong-lin Huang; Rui-jie He; Bing-yuan Yang; Zhang-bin Liu (Natural Product Research, 2023)

Triassic convergence and tectonic evolution of the West Qinling orogen: Constraints from reflection-seismology imaging - Huilin Li; Rui Gao; Xingfu Huang; Haiyan Wang; Xiaoyu Guo; Hongda Liang; Xiaomiao Tan; Xiaohui Liu; Zhen Yang (Gondwana Research, 2023)

The effect of stabilized culture of Lactobacillus rhamnosus GCC-3 on gut and liver health, and anti-viral immunity of zebrafish - Hui Liang; Yadong Xie; Ming Li; Jie Chen; Wenhao Zhou; Rui Xia; Qianwen Ding; Yuanyuan Yao; Zhen Zhang; Yalin Yang; Chao Ran; Zhigang Zhou (Fish & Shellfish Immunology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

A quasi-one-dimensional bulk thermoelectrics with high performance near room temperature - Qingxin Dong; Junsen Xiang; Zhen Wang; Yunxiu Li; Rui Lu; Te Zhang; Nan Chen; Yifei Huang; Yiyan Wang; Wenliang Zhu; Guodong Li; Huaizhou Zhao; et al. (Science Bulletin, 2023)

Tetrathiafulvalene as a sustainable cathode with high rate and Long Life-span for aqueous Zinc-ion battery at low temperatures - Jiayao Wang; Xinyi Zhang; Zehua Yan; Zhen Rui; Ze Yang; Yongxin Huang; Wenwen Deng (Chemical Engineering Journal, 2023)

Sulfite altered permanganate effects on acetate-enriched short-chain fatty acids production during sludge anaerobic fermentation - Lijuan Wu; Rui Zhu; Xiaoxia Han; Yan Chen; Zhen Long; Hao Dong; Xiaojiang Chen; Yang Wu; Yinglong Su; Zhengyong Zhang; Jingyang Luo (Bioresource Technology, 2023)

Salicylic acid enhances the resistance of Neoporphyra haitanensis to pathogen Vibrio mediterranei 117-T6 - Shanshan Zhu; Zhen Jin; Juanjuan Chen; Rui Yang; Qijun Luo; Tiegan Wang; Peng Zhang; Haimin Chen (Aquaculture, 2023)

Azospirillum Endophyticum sp. nov., an Endophyte of Paris Polyphylla Smith var. Yunnanensis - Peng-Chao Zhan; Rui-Feng Mao; Cong-Jian Li; Zhen Zhang; Jing-Ran Liu; Mei Tang; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2023)

Proteome Based Comparative Investigation of a High Sucrose Sugarcane Mutant in Contrast to the Low Sucrose Mother Variety by Using TMT Quantitative Proteomics - Qaisar Khan; Ying Qin; Dao-Jun Guo; Zhen Lu; Xian-Qiu Xie; Li-Tao Yang; Qiang Liang; Xiu-Peng Song; Yong-Xiu Xing; Yang-Rui Li (Sugar Tech, 2022)

Activation of the TREK-1 Potassium Channel Improved Cognitive Deficits in a Mouse Model of Alzheimer’s Disease by Modulating Glutamate Metabolism - Fang Li; Shu-ning Zhou; Xin Zeng; Zhen Li; Rui Yang; Xue-xi Wang; Bin Meng; Wei-lin Pei; Li Lu (Molecular Neurobiology, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Dysfunction of FadA‐cAMP signalling decreases Aspergillus flavus resistance to antimicrobial natural preservative Perillaldehyde and AFB1 biosynthesis - Kunlong Yang; Qingru Geng; Yue Luo; Rui Xie; Tongzheng Sun; Zhen Wang; Ling Qin; Wei Zhao; Man Liu; Yongxin Li; Jun Tian (Environmental Microbiology, 2022)
Summary Aspergillus flavus is an opportunistic fungal pathogen that colonizes agriculture crops with aflatoxin contamination. We found that Perillaldehyde (PAE) effectively inhibited A . flavus viability and aflatoxin production by inducing excess reactive oxygen species (ROS). Transcriptome analysis indicated that the Gα protein FadA was significantly induced by PAE. Functional characterization of FadA showed it is important for asexual development and aflatoxin biosynthesis by regulation of cAMP‐PKA signalling. The Δ fadA mutant was more sensitive to PAE, while Δ pdeL and Δ pdeH mutants can tolerate excess PAE compared to wild‐type A . flavus . Further RNA‐sequence analysis showed that fadA was important for expression of genes involved in oxidation–reduction and cellular metabolism. The flow cytometry and fluorescence microscopy demonstrated that Δ fadA accumulated more concentration of ROS in cells, and the transcriptome data indicated that genes involved in ROS scavenging were downregulated in Δ fadA mutant. We further found that FadA participated in regulating response to extracellular environmental stresses by increasing phosphorylation levels of MAPK Kinase Slt2 and Hog1. Overall, our results indicated that FadA signalling engages in mycotoxin production and A . flavus resistance to antimicrobial PAE, which provide valuable information for controlling this fungus and AF biosynthesis in pre‐ and postharvest of agricultural crops.

Toward Exploring Topographic Effects on Evolution and Propagation of Ocean Mesoscale Eddies Through Life Cycle Across Izu-Ogasawara Ridge in Northwestern Pacific Ocean - Rui Nian; Xue Geng; Zhengguang Zhang; Minghan Yuan; Zhen Fu; Hengfu Xu; Hua Yang; Qi Lai; Hui He; Chi Wei Su; Lina Zang; Qiang Yuan; et al. (Frontiers in Marine Science, 2022)
Ocean mesoscale eddies contribute significantly to water transport on a global scale, constituting the ubiquitous, irregular, discrete, nonlinear components. In this manuscript, we propose to explore whether and how the topographic effect of one meridional ridge, could exert considerable influences on the evolution and propagation of mesoscale eddies through their life cycle, directly from the perspectives of real observation statistics. We systematically investigate the known variability of mesoscale eddy trajectories, derived by multimission satellite altimetry from 1993 to 2018, of a life cycle more than 6 months, over the Izu-Ogasawara Ridge, and quantitatively examined the eddy-ridge interaction by observation statistics and wavelet coherence map, with respect to the intrinsic attributes, namely, the amplitude, the rotation speed, the radius. Due to the spatial-temporal diversity, a series of correlative steps have been particularly designed along time-frequency domain to trace back mesoscale eddy trajectories in a variety of origins, location, lifespan, polarity, either completely or partially passing over the ridge, and to facilitate the standardization in statistics across three phases of their life cycle, i.e., before, during and after the interaction with the ridge. It has been revealed in our experiment that three intrinsic attributes of mesoscale eddies within 25 years, all demonstrated noticeable correlation with the variation of topographic relief over the ridge. We observed that most of the cyclonic eddies obviously tended to begin to decay or even demise, while on the contrary, some of the anticyclonic eddies preferred to intensify slightly, or making no significant difference when encountering the upslope until climbing across the top, basically consistent with the expectation of potential vorticity (PV) conservation. The drifting velocity agreed with the tendency that the direction would be more probably modified toward equatorward or poleward by forcing to meridional component, with zonal component reduced at the beginning. The mesoscale eddies with the passage over the ridge exhibited the relatively high average horizontal scales, amplitude, rotation speed on the whole, compared to those with only partially passage. The developed scheme could integrate more evidences on how mesoscale eddies response to the topographic effects during their time-varying evolution and propagation process, and help provide opportunities to potentially identify and predict the underlying dynamic patterns and mechanisms that mesoscale eddies engage in ocean dynamics when proceeding toward meridional ridges on a global scale, with the promise of the end-to-end data-driven solution, such as deep learning architecture involved in the future.

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Correction to: Temporal and spatial evolution patterns of drought in China over the past 500 years - Cuixia Wei; Bing Guo; Wenqian Zang; Fei Yang; Yuefeng Lu; Dafu Zhang; Hongwei Wu; Xiaoyan Zhen; Haorun Xue; Chao Meng; Shuting Chen; Xiao Yang; et al. (Arabian Journal of Geosciences, 2021)

Genomic molecular signatures determined characterization of Mycolicibacterium gossypii sp. nov., a fast-growing mycobacterial species isolated from cotton field soil - Rui-Rui Huang; Shen-Rong Yang; Cheng Zhen; Xian-Feng Ge; Xin-Kai Chen; Zhi-Qiang Wen; Ya-Nan Li; Wen-Zheng Liu (Antonie van Leeuwenhoek, 2021)

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

A New Approach to Embed Complex Fracture Network in Tight Oil Reservoir and Well Productivity Analysis - Jiaxiang Xu; Lifeng Yang; Zhe Liu; Yunhong Ding; Rui Gao; Zhen Wang; Shaoyuan Mo (Natural Resources Research, 2021)

How the variations of terrain factors affect the optimal interpolation methods for multiple types of climatic elements? - Bing Guo; Fei Yang; Hongwei Wu; Rui Zhang; Wenqian Zang; Cuixia Wei; Guangmao Jiang; Chao Meng; Huihui Zhao; Xiaoyan Zhen; Dafu Zhang; Hailing Zhang (Earth Science Informatics, 2021)

Temporal and spatial evolution patterns of drought in China over the past 500 years - Cuixia Wei; Bing Guo; Wenqian Zang; Fei Yang; Yuefeng Lu; Dafu Zhang; Hongwei Wu; Xiaoyan Zhen; Haorun Xue; Chao Meng; Shuting Chen; Xiao Yang; et al. (Arabian Journal of Geosciences, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Advances of intra‐species molecular typing analysis of aquatic probiotics approved by the Chinese Ministry of Agriculture - Juan Hu; Yuanyuan Yao; Yalin Yang; Chenchen Gao; Fengli Zhang; Rui Xia; Chao Ran; Zhen Zhang; Jihong Liu Clarke; Zhigang Zhou (Reviews in Aquaculture, 2021)
Probiotics confer a health benefit on the host and could be used as a good alternative to antibiotics. Probiotics are strain‐specific when exerting their function, so it is necessary to identify them to strain level. In recent years, intra‐species molecular typing and identification methods have developed rapidly, which commonly are used for typing the main pathogenic bacteria and rare for studies on probiotic typing, whilst it is imperative. This article describes molecular typing methods including AFLP, RAPD, PFGE, ribotyping, MLST, rep‐PCR and whole‐genome sequencing to identity some aquatic probiotics approved by the Ministry of Agriculture of China, which are Bifidobacterium , Enterococcus , Lactobacillus , Pediococcus , Aspergillus , Bacillus , Rhodopseudomonas palustris and Streptococcus thermophilus . In addition, the principles, applications, advantages and disadvantages of these typing methods are also discussed.

Surface display system for probiotics and its application in aquaculture - Yuan‐Yuan Yao; Ya‐Lin Yang; Chen‐Chen Gao; Feng‐Li Zhang; Rui Xia; Dong Li; Juan Hu; Chao Ran; Zhen Zhang; Jihong Liu‐Clarke; Zhi‐Gang Zhou (Reviews in Aquaculture, 2020)
Aquaculture is a fast‐growing and rapidly expanding industry in the world. Probiotics are widely used in aquaculture and have provided benefits to aquatic animal health, and it is also a promising alternative to antibiotics for control of fish diseases. With the development of biotechnology, new expression systems and novel techniques for the surface display of heterologous proteins in surface of probiotics cells have been developed. This review provides an overview of the systems and strategies for displaying functional proteins on the surface of probiotics commonly used in aquaculture, which are Bacillus subtilis , Bacillus thuringiensis , lactic acid bacteria represented by Lactococcus lactis and yeast. Their applications in aquaculture especially for oral vaccine development afforded by this technology and prospects and challenges associated with this technology are also highlighted.

Intrusion of Fall Armyworm (Spodoptera frugiperda) in Sugarcane and Its Control by Drone in China - Xiu-Peng Song; Yong-Jian Liang; Xiao-Qiu Zhang; Zhen-Qiang Qin; Jin-Ju Wei; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2020)

Effects of Spray Parameters of Drone on the Droplet Deposition in Sugarcane Canopy - Xiao-Qiu Zhang; Xiu-Peng Song; Yong-Jian Liang; Zhen-Qiang Qin; Bao-Qing Zhang; Jin-Ju Wei; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2020)

Impact of Sugarcane–Legume Intercropping on Diazotrophic Microbiome - Manoj Kumar Solanki; Fei-Yong Wang; Chang-Ning Li; Zhen Wang; Tao-Ju Lan; Rajesh Kumar Singh; Pratiksha Singh; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2020)

The giant Zaozigou Au-Sb deposit in West Qinling, China: magmatic- or metamorphic-hydrothermal origin? - Kun-Feng Qiu; Hao-Cheng Yu; Jun Deng; Duncan McIntire; Zong-Yang Gou; Jian-Zhen Geng; Zhao-Shan Chang; Rui Zhu; Kang-Ning Li; Richard Goldfarb (Mineralium Deposita, 2020)

Yeast cell walls stimulate viability, respiratory burst, and phagocytosis in channel catfish (Ictalurus punctatus) head-kidney macrophages - Jianjun Zhou; Zhen Gao; Wenbiao Wang; Feng Huang; Junpeng Hu; Aqiong Gong; Rui Wang; Wumin Yang; Jie Li; Xianqin Hu; Xuedong Wang (Aquaculture International, 2019)

Application of Multi-rotor Unmanned Aerial Vehicle Application in Management of Stem Borer (Lepidoptera) in Sugarcane - Xiao-Qiu Zhang; Yong-Jian Liang; Zhen-Qiang Qin; De-Wei Li; Chun-Yan Wei; Jin-Ju Wei; Yang-Rui Li; Xiu-Peng Song (Sugar Tech, 2019)

Rhizospheric and endospheric diazotrophs mediated soil fertility intensification in sugarcane-legume intercropping systems - Manoj Kumar Solanki; Fei-Yong Wang; Zhen Wang; Chang-Ning Li; Tao-Ju Lan; Rajesh Kumar Singh; Pratiksha Singh; Li-Tao Yang; Yang-Rui Li (Journal of Soils and Sediments, 2019)

Cloning and Identification of Differentially Expressed Genes Associated with Smut in Sugarcane - Xiu-Peng Song; Dan-Dan Tian; Ming-Hui Chen; Zhen-Qiang Qin; Jin-Ju Wei; Chun-Yan Wei; Xiao-Qiu Zhang; De-Wei Li; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2018)

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

Petrogenesis and Ore Genesis of the Late Yanshanian Granites and Associated Porphyry-Skarn W-Mo Deposits from the Yunkai Area of South China: Evidence from the Zircon U-Pb Ages, Hf Isotopes and Sulfide S-Fe Isotopes - Xinyu Wang; Zhen Yang; Nengsong Chen; Rui Liu (Journal of Earth Science, 2018)

Least squares reverse-time migration in the pseudodepth domain and reservoir exploration - Xiao-Dong Sun; Yan-Rui Jia; Min Zhang; Qing-Yang Li; Zhen-Chun Li (Applied Geophysics, 2018)

Geochronology, geochemistry, and Sr–Nd–Pb–Hf isotopes of the Zhunsujihua granitoid intrusions associated with the molybdenum deposit, northern Inner Mongolia, China: implications for petrogenesis and tectonic setting - Xiaojun Zhang; David R. Lentz; Chunliang Yao; Rui Liu; Zhen Yang; Yanxiong Mei; Xianwang Fan; Fei Huang; Ying Qin; Kun Zhang; Zhenfei Zhang (International Journal of Earth Sciences, 2018)

Differential Effects of Cold Stress on Chloroplasts Structures and Photosynthetic Characteristics in Cold-Sensitive and Cold-Tolerant Cultivars of Sugarcane - Su-Li Li; Zhi-Gang Li; Li-Tao Yang; Yang-Rui Li; Zhen-Li He (Sugar Tech, 2018)

Structural Transformation Detection Contributes to Screening of Behaviorally Active Compounds: Dynamic Binding Process Analysis of DhelOBP21 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Guangqiang Yu; Shan-Cheng Yi; Yinan Zhang; De-Xin Kong; Man-Qun Wang (Journal of Chemical Ecology, 2017)

Phenylpropanoids from the fruits of Nicandra physaloides and their anti-inflammatory activities - Bing You Yang; Yan Liu; Hai Bing Jiang; Zhen Peng Xu; Rui Guo; Rui Wang; Xiao Mao Li; Hai Xue Kuang (Natural Product Research, 2017)

Identification and Efficiency of a Nitrogen-fixing Endophytic Actinobacterial Strain from Sugarcane - Zhen Wang; Manoj Kumar Solanki; Fei Pang; Rajesh Kumar Singh; Li-Tao Yang; Yang-Rui Li; Hai-Bi Li; Kai Zhu; Yong-Xiu Xing (Sugar Tech, 2017)

Intercropping in Sugarcane Cultivation Influenced the Soil Properties and Enhanced the Diversity of Vital Diazotrophic Bacteria - Manoj Kumar Solanki; Zhen Wang; Fei-Yong Wang; Chang-Ning Li; Tao-Ju Lan; Rajesh Kumar Singh; Pratiksha Singh; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2017)

Neuroprotective Role of MicroRNA-22 in a 6-Hydroxydopamine-Induced Cell Model of Parkinson’s Disease via Regulation of Its Target Gene TRPM7 - Chao Ping Yang; Zhen Hua Zhang; Li Hua Zhang; Han Chen Rui (Journal of Molecular Neuroscience, 2016)

Molecular cloning and characterization of the MsHSP17.7 gene from Medicago sativa L. - Zhen-yi Li; Rui-cai Long; Tie-jun Zhang; Qing-chuan Yang; Jun-mei Kang (Molecular Biology Reports, 2016)

Inoculation of Fe/Mn-oxidizing bacteria enhances Fe/Mn plaque formation and reduces Cd and As accumulation in Rice Plant tissues - Ming Fang Dong; Ren Wei Feng; Rui Gang Wang; Yang Sun; Yong Zhen Ding; Ying Ming Xu; Zhi Lian Fan; Jun Kang Guo (Plant and Soil, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

The Prevention Effect of Selenium on Prevalence of Children Kaschin-Beck Disease in Active Endemic Areas in Qinghai Plateau - Qiang Li; Zhi-jun Zhao; Pei-zhen Yang; Xiao-qing Xu; Yu-fang Liu; Hui-zhen Yu; Xiao Ma; Rui Du; Lei Zhu (Biological Trace Element Research, 2016)

Brittleness index and seismic rock physics model for anisotropic tight-oil sandstone reservoirs - Xin-Rui Huang; Jian-Ping Huang; Zhen-Chun Li; Qin-Yong Yang; Qi-Xing Sun; Wei Cui (Applied Geophysics, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Clinical and angiographic features associated with coronary collateralization in stable angina patients with chronic total occlusion - Zhen Sun; Ying Shen; Lin Lu; Rui-yan Zhang; Li-jin Pu; Qi Zhang; Zheng-kun Yang; Jian Hu; Qiu-jing Chen; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2013)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Scutellarin exerts its anti-hypertrophic effects via suppressing the Ca2+-mediated calcineurin and CaMKII signaling pathways - Zhen-Wei Pan; Ying Zhang; Dong-Hua Mei; Rui Zhang; Jing-Hao Wang; Xiang-Ying Zhang; Chang-Qing Xu; Yan-Jie Lu; Bao-Feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Trehalose synthase gene transfer mediated byAgrobacterium tumefaciens enhances resistance to osmotic stress in sugarcane - Zi-Zhang Wang; Shu-Zhen Zhang; Ben-Peng Yang; Yang-Rui Li (Sugar Tech, 2005)